Incorporação e apropriação dos resultados de uma intervenção ergonômica: um estudo de caso - Cockell, Fernanda Flavia (2004)
The recent changes in the work s world have modified and amplified the performance field of the ergonomics. Through a brief methodological discussion about the Ergonomic Work Analysis and a bibliographical revision about undertaken ergonomic interventions, it was verified that the results of work transformation through Ergonomic Work Analysis not always will be positive. Consequently, this work had an objective of analyzing an ergonomic intervention accomplished in a powdered detergent company, due to understand how ergonomic actions are incorporated for the different social actors and how the company, through the management, could appropriate of the results in behalf of the production. The process of activity transformation of the Vincador, from the initial demand for recommendations implemetation and validation, as well as the established social relationships and the Vincadores roles, managers, Internal Committee of Ergonomics and the company were analyzed under the Ergonomic Work Analysis point of view. The results showed that Vincadores work rhythm has increased after the ergonomic recommendations implemetation as a consequence of management s appropriation of regulations margins, whose intention was to increase the process effectiveness without considering the balance between health versus productivity. The non-incorporation of the activity point of view helped, therefore, that changes of interests, values and the involved actors logic s, lead to commitment break, before firmed among those, turning the new situation noxious for the Vincadores health.